2023
DOI: 10.3390/antibiotics12040704
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Enterococcus faecalis Infective Endocarditis: A Continuing Challenge

Abstract: Today, Enterococcus faecalis is one of the main causes of infective endocarditis in the world, generally affecting an elderly and fragile population, with a high mortality rate. Enterococci are partially resistant to many commonly used antimicrobial agents such as penicillin and ampicillin, as well as high-level resistance to most cephalosporins and sometimes carbapenems, because of low-affinity penicillin-binding proteins, that lead to an unacceptable number of therapeutic failures with monotherapy. For many … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 220 publications
1
4
0
Order By: Relevance
“…We have summarized the clinical features, renal status, and outcome in Table 2, including our case report. The findings of Pericas et al [3] and Herrera-Hidalgos et al [27] contemporary reviews align with our data presented in Table 2. They demonstrate that Enterococcal endocarditis is the second most prevalent cause of infective endocarditis within the chronic hemodialysis population, trailing behind only Staphylococcus aureus with percentages of 15.4% and 47.8%, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…We have summarized the clinical features, renal status, and outcome in Table 2, including our case report. The findings of Pericas et al [3] and Herrera-Hidalgos et al [27] contemporary reviews align with our data presented in Table 2. They demonstrate that Enterococcal endocarditis is the second most prevalent cause of infective endocarditis within the chronic hemodialysis population, trailing behind only Staphylococcus aureus with percentages of 15.4% and 47.8%, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…However, ampicillin and vancomycin resistance necessitates the use of other antibiotics. 22 In the current study, significant ampicillin resistance rate was found for E. faecium strains. However, no significant difference was detected in terms of the resistance against ampicillin.…”
Section: Discussionmentioning
confidence: 46%
“…Following this therapeutic regimen, EIPs could be prepared and dispensed twice a week, favoring their transfer for use in OPAT for the treatment of infections such as endocarditis or osteomyelitis. In the case of endocarditis, these results are particularly relevant since they position the dual therapy of AMP and ceftriaxone for its use in OPAT against other novel and more expensive antibiotics with promising characteristics like teicoplanin or dalbavancin, whose usefulness in the outpatient management of infective endocarditis caused by Enterococcus faecalis is still not sufficiently justified to make a new recommendation or to implement a safe and effective outpatient treatment protocol [ 45 , 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%